Diffusion tensor imaging and apparent diffusion coefficient values of hippocampal formation in medically intractable temporal lobe epilepsy patients - Jalil, Farouk (2017)
Objective: The purpose of this study is to determine whether interictal DTI and apparent diffusion coefficients (ADC) provide a robust means for detecting hippocampal formation abnormalities in patients with medically intractable temporal lobe epilepsy (TLE). Methodology: Fourteen patients and 14 controls were studied with hippocampal formation ADC maps, fractional anisotropy and Trace D values. MR images were evaluated for loss of volume and/or high signal intensity on T2-weighted images and compared with DTI and ADC maps. Mean and SDs were obtained for each measurement, and level of significance was determined (P < .05). The relationship between EEG lateralization and MR imaging and DTI/ADCs were studied. Results : Ten patients had right-sided lateralization and 4 had left-sided lateralization on EEG. Patients demonstrated higher ADC within the diseased hippocampus (0.54 x 10-3 s/mm2) in comparison with the contralateral side and that of controls (0.39 x10- 3s/mm2 and 0.40 x 10-3s/mm2, respectively) (P < .05). Positive correlations were seen between hippocampal apparent diffusion coefficients and fractional anisotropy (P < .05). Conclusion : ADC and DTI have the capabilities to detect changes in the hippocampal formation and to lateralize the seizure focus in patients with TLE despite absence of morphological changes on conventional MRI sequence.